Physicochemical and functional properties of silver carp (Hypophthalmichthys molitrix) myofibrillar protein glycated with konjac oligo-glucomannan. (June 2017) - Liu, Shulai; Zhao, Peicheng; Zhang, Jingjing; Xu, Qiuhong; Ding, Yuting; Liu, Jianhua
Abstract: Konjac oligo-glucomannan (KOG) is a new-type polysaccharide with abundant hydroxyl groups and a small quantity of branches. Myofibrillar protein (Mf) from silver carp ( Hypophthalmichthys molitrix ) was incubated with KOG for 0–96 h at 50 °C and 75% relative humidity to obtain glycoconjugates in different periods of Maillard reaction. Physicochemical properties, including SDS-PAGE, sugars bound to Mf, available amino acids and FT-IR property all indicated that glycation occurred successfully. In addition, activity of Ca 2+ -ATPase decreased markedly due to thermal denaturation and glycation of Mf. Functional properties of Maillard reaction productions (MRPs), such as solubility, heat stability and emulsion properties were all superior to Mf. Solubility and emulsion properties reached the highest value at 8–12 h of the reaction, and then decreased severely. However, heat stability decreased at 2–5 h of glycation, and then increased significantly. In conclusion, KOG is an excellent sugar donator to improve functional properties of Mf by glycation. Graphical abstract: Highlights: KOG is a new-type polysaccharide prepared by degradation of KGM using β-mannanase. KOG has abundant hydroxyl groups and displays great steric hindrance. Physicochemical properties proved glycation of myofibrillar and KOG successful. Functional properties could be improved markedly by glycation with KOG. KOG is an excellent sugar donator to glycate with myofibrillar.